Persepsi Masyarakat Desa Terhadap Perbankan Syariah di Kabupaten Indramayu : (Studi pada Masyarakat Desa Langut, Kecamatan Lohbener, Kabupaten Indramayu) - Nuni Oktaviani; M. Farhan Hidayat (LPPM STAIS Dharma Indramayu, 2019)
The establishment of Islamic banks is an indication of the decline of the interest and usury system. This was confirmed by the issuance of the MUI fatwa (16-12-2013) regarding the prohibition of interest and usury in muamalah activities. The issuance of MUI fatwas regarding Islamic economics has had an influence in increasing the strength of the existence of sharia banking amidst the growth of banking business activities in Indonesia. The existence of banking as a financial service is based on public trust (Yadi, 2015). Understanding and outreach to the public regarding sharia banking products and systems in Indramayu Regency is still very limited. This is proven by observations made by researchers in Langut village that very few people know about sharia banking products in Indramayu. Reporting from data from the Central Statistics Agency for Indramayu Regency, it shows that Indramayu is still dominated by Muslims. This also supports the development of sharia banking in Indramayu, especially for village communities. From the background of the problems described above, problems arise which will later be used as a reference in conducting research in this matter: Various Perceptions of the Langut Village Community Regarding Sharia Banking in Indramayu Regency. The research that the researcher conducted was descriptive research with a qualitative approach. The subject of this research was a sharia bank in Indramayu. Meanwhile, the research object was the village community where the researcher took the research location in a village in Indramayu, namely Langut village, Lohbener subdistrict, Indramayu district. The public's perception of the existence of sharia banks is in the Medium category, meaning that people do not really understand what sharia banks are like, people already know about sharia banks but don't understand them, they just know, people still have the opinion that sharia banks are no different from conventional banks. , the public does not yet understand what the advantages of Islamic banks are compared to conventional banks. This can be seen through the continuum line, the score obtained for public perception of the existence of Islamic banks is 1,781 with a percentage of 59.36% of the expected ideal score of 3,000.